2002
DOI: 10.1007/s11745-002-0893-3
|View full text |Cite
|
Sign up to set email alerts
|

Lung lipid composition in zinc‐deficient rats

Abstract: There have been a limited number of studies investigating surfactant lipid changes in lung with trace elements. The present investigation was designed to examine the effect of moderate zinc deficiency on the lipid metabolism in rat lung. We also evaluated whether zinc deficiency, which is a wide-spread problem, could play a role in adult respiratory distress syndrome (ARDS). For that purpose, adult male Wistar rats were fed two diets differing in zinc concentration. The rats were divided into two groups. One g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
15
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 43 publications
3
15
0
Order By: Relevance
“…Animal studies have demonstrated that zinc deficiency may affect lung and airway cells 3–7 and lead to more severe lung damage 5 . In a previous report of non‐critically ill elderly, normal compared with low serum zinc decreased the duration of pulmonary infections 9 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Animal studies have demonstrated that zinc deficiency may affect lung and airway cells 3–7 and lead to more severe lung damage 5 . In a previous report of non‐critically ill elderly, normal compared with low serum zinc decreased the duration of pulmonary infections 9 .…”
Section: Discussionmentioning
confidence: 97%
“…Zinc may have a role in maintaining pulmonary epithelial cell integrity 3–5 . In addition, zinc deficiency in animal models changes lipid metabolism in lungs, 6 and may lead to pulmonary oedema by increasing pulmonary capillary permeability 7 . Anti‐inflammatory and anti‐oxidant effects of zinc may protect pulmonary epithelial cells during oxidative stress 8 …”
mentioning
confidence: 99%
“…This coincided with a high expression of CT-α mRNA. The increased aorta cholesterol content could lead to an enhanced expression of CT-α mRNA [39, 40]. In addition, the increased fatty acid synthesis observed in the aorta of vitamin-A-deficient rats suggests a high availability of fatty acids to form PL.…”
Section: Discussionmentioning
confidence: 99%
“…The major phospholipid component (at the air-liquid interface) is phosphatidylcholine (70–80%) and numerous reports indicate that changes in phosphatidylcholine metabolism are a common feature of the pathophysiology of experimental chronic lung injury or adult respiratory distress syndrome. A moderate Zn deficiency ( in vivo ) can induce a physiological stimulus that enhances phospholipid synthesis and changes especially the pattern of phospholipids in adult rat lung [122,123]. …”
Section: Zinc On Phospholipid Metabolismmentioning
confidence: 99%